Bond Index Approach to the Evaluation of Transportation P3 Market in the U.S. Issue 6 (June 2020) - Wang, Yu; Zhang, Kunqi; Cui, Qingbin; Delgado, Felix
Private investment through revenue bonds has become an important source of financing for public agencies seeking to implement public–private partnership (P3) projects. It has been a long-standing assumption that private financing exceeds the limited investment opportunity attributed to P3 projects in the pipeline. This assumption, however, remains unexamined. Basic economics theory states that prices go up if demand exceeds supply. Therefore, this study presents the construction and performance of the P3 surface transportation bond index to evaluate private capital for P3 projects. The index will help encourage private investment in P3 projects in addition to measuring the return of such investment on a market basis. The index can also disclose the risks of P3 revenue bonds and potentially offer an investment instrument in the secondary market.